An Analysis of the Validity of Digital Evidence in the Modern Technological Era - Fauziah Lubis; Halwa Shabri, Indana; Siti Adinda Puspita; Chairun Nissa Eprianty; Trisnanda Rielta; Jannatun Naim (SEAN Institute, 2025)
The increasing reliance on digital technology in legal processes has transformed the nature of evidence presented in courtrooms. However, this transformation introduces serious challenges in verifying the authenticity and admissibility of electronic data, which is often more prone to alteration than traditional physical evidence. This study aims to examine how digital evidence is legally recognized and validated within Indonesia's civil litigation framework, particularly under the Positief Wettelijk Bewijs doctrine, which emphasizes formal legal standards in evidence evaluation.The research was conducted using normative legal methodology, focusing on statutory analysis and legal doctrine review. Various sources, including Indonesian legislation such as the Electronic Information and Transactions Law (ITE Law), scholarly articles, and international best practices in digital forensics, were examined to provide a comprehensive legal understanding. Findings reveal that while Indonesia formally acknowledges digital evidence through existing regulations, the practical implementation faces multiple obstacles. These include the absence of standardized procedures, inconsistencies in institutional interpretation, and a lack of technical competence among legal practitioners. Furthermore, the legal system’s formalistic orientation often clashes with the dynamic and complex nature of digital data, limiting its evidentiary value in court. To address these issues, the study emphasizes the urgency of legal reform both in terms of regulatory updates and the enhancement of forensic capabilities within the judiciary. Strengthening the legal infrastructure and aligning it with technological realities is essential to ensure the fair and effective use of electronic evidence in civil judicial proceedings.